2012
DOI: 10.1016/j.dci.2011.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility polymorphism in snail/schistosome interactions: From field to theory to molecular mechanisms

Abstract: Coevolutionary dynamics in host–parasite interactions potentially lead to an arms race that results in compatibility polymorphism. The mechanisms underlying compatibility have remained largely unknown in the interactions between the snail Biomphalaria glabrata and Schistosoma mansoni, one of the agents of human schistosomiasis. This review presents a combination of data obtained from field and laboratory studies arguing in favor of a matching phenotype model to explain compatibility polymorphism. Investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 63 publications
9
90
0
3
Order By: Relevance
“…The infection rate was quite heterogeneous in the present study, with differences observed both between the two species and within the same species, thus confirming the important polymorphism of the susceptibility of Biomphalaria species [10, 2022]. These results likely indicate an important genetic diversity among snail populations as was previously observed in Cameroon [12] and Madagascar [23].…”
Section: Compatibilitysupporting
confidence: 89%
See 1 more Smart Citation
“…The infection rate was quite heterogeneous in the present study, with differences observed both between the two species and within the same species, thus confirming the important polymorphism of the susceptibility of Biomphalaria species [10, 2022]. These results likely indicate an important genetic diversity among snail populations as was previously observed in Cameroon [12] and Madagascar [23].…”
Section: Compatibilitysupporting
confidence: 89%
“…These results likely indicate an important genetic diversity among snail populations as was previously observed in Cameroon [12] and Madagascar [23]. The highest infection rate was observed in the sympatric pair B. pfeifferi / S. mansoni of Nkolbisson, suggesting that this parasite is best adapted to its local snail population as previously described [15, 22], though local adaptation is not always the rule [24]. This parasite strain seems to be less adapted to the population of northern Cameroon (Gounougou and Mokolo) as supported by the significantly high mortality rate in S. mansoni- infected snails belonging to these populations.…”
Section: Compatibilitysupporting
confidence: 82%
“…The ability of the helminth Schistosoma mansoni to successfully infect its intermediate snail host trades-off with success at infecting its definitive mouse host (Davies et al, 2001). This suggests some of the genes associated with infecting snails may also influence infection success in mice and that antagonistic pleiotropic effects could maintain allelic diversity in these genes (Webster and Woolhouse, 1998;Davies et al, 2001;Webster et al, 2007;Mitta et al, 2012). The tapeworm, Schistocephalus solidus exhibits a slightly different trade-off between its ability to overcome the innate immune system (present in both invertebrates and vertebrates) and the acquired immune system (present in vertebrates only; Hammerschmidt and Kurtz, 2005).…”
Section: Mechanisms Of Infection and Host Immune Evasion In Clps: Difmentioning
confidence: 99%
“…Plasmodium falciparum even exhibits genetic specificity with its Anopheles gambiae (mosquito) hosts, where infection success depends on the exact combination of P. falciparum strain and mosquito genotype (Lambrechts et al, 2005). Schistosoma mansoni also shows evidence of genetic specificity with its snail intermediate host, Biomphalaria glabrata (Webster and Woolhouse, 1998;Davies et al, 2001;Mitta et al, 2012), and Microphallus trematodes exhibit adaptation to locally common genotypes of their snail intermediate hosts, Potamopygus antipodarum (Lively and Dybdahl, 2000;Dybdahl et al, 2008;Jokela et al, 2009).…”
Section: Clps and Host-parasite Coevolutionmentioning
confidence: 99%
“…Such local adaptation relies on the interplay of highly variable proteins of hosts and parasites [118]. With this in mind, underlying genetic changes in the population can occur quite rapidly.…”
Section: Lack Of Population Genetic Structure In O Felineusmentioning
confidence: 99%